2016
DOI: 10.3892/ijo.2016.3398
|View full text |Cite|
|
Sign up to set email alerts
|

Tripartite motif 16 inhibits hepatocellular carcinoma cell migration and invasion

Abstract: Tripartite motif 16 (TRIM16), a member of the RING B-box coiled-coil (RBCC)/tripartite totif (TRIM) protein family, has been demonstrated to have significant effects on tumor migration by previous studies, but its specific contribution to hepatocellular carcinoma (HCC) is currently unknown. The aim of this study was to evaluate the prognostic value of TRIM16 and investigate its functional roles in HCC. The expression of TRIM16 in HCC patient samples were examined using qRT-PCR and western blotting. HCC cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 18 publications
2
26
1
2
Order By: Relevance
“…TRIM16, also named as the estrogen responsive B box protein (EBBP), has been shown to play a negative role in the development and progression of several cancers. For example, the expression of TRIM16 is significantly down-regulated in HCC and knockdown of TRIM16 enhances HCC cell migration and invasion via the promotion of EMT process [36]. TRIM16 is also at low levels in prostate tumors and enforced expression of TRIM16 inhibits prostate cancer cell migration and invasion in a manner associated with the inhibition of Snail signaling pathway and EMT process [37].…”
Section: Trim16mentioning
confidence: 99%
“…TRIM16, also named as the estrogen responsive B box protein (EBBP), has been shown to play a negative role in the development and progression of several cancers. For example, the expression of TRIM16 is significantly down-regulated in HCC and knockdown of TRIM16 enhances HCC cell migration and invasion via the promotion of EMT process [36]. TRIM16 is also at low levels in prostate tumors and enforced expression of TRIM16 inhibits prostate cancer cell migration and invasion in a manner associated with the inhibition of Snail signaling pathway and EMT process [37].…”
Section: Trim16mentioning
confidence: 99%
“…При этом уровень матричной РНК (мРНК) гена TRIM16 и количество белка были снижены у больных раком легкого с наличием метастазов по сравнению с пациентами без них [11]. Сходные результаты получены при исследовании больных гепатоцеллюлярным раком [12]. Надо отметить, что зафиксированы противоположные данные по отношению к культуре опухолевых клеток яичника, где гиперэкспрессия TRIM16 способствует снижению уровня мРНК Nкадгерина и виментина, являющихся мезенхимальными маркерами, и повышению уровня мРНК белка Е-кадгерина, относящегося к эпителиальным маркерам [6].…”
Section: роль Trim16 в регуляции внутриклеточных процессовunclassified
“…Уровень белка существенно ниже в опухолевой ткани предстательной железы по сравнению с нормальной [21]. Показана связь TRIM16 с развитием и прогрессированием рака яичника [6], плоскоклеточных карцином области головы и шеи [7], рака легкого [11], гепатоцеллюлярного рака [12]. Эти факты позволяют рассматривать высокую экспрессию данного белка в качестве маркера благоприятного исхода заболевания [4,15].…”
Section: рис 1 значение Trim16 в развитии злокачественных новообразunclassified
“…TRIM genes have been subclassified based on differences in their C-terminal domains [6][7][8]. Recent studies have shown that several TRIM proteins are involved in the tumorigenesis and development of solid malignancies, including hepatocellular carcinoma (HCC) [9][10]. For example, TRIM24 can function as a liver-specific tumour suppressor in mice and co-regulate hepatocarcinogenesis in an Ivyspring International Publisher antagonistic manner with Rara [9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, TRIM24 can function as a liver-specific tumour suppressor in mice and co-regulate hepatocarcinogenesis in an Ivyspring International Publisher antagonistic manner with Rara [9]. In addition, TRIM16 has been proven to inhibit cell migration, invasion and epithelial-mesenchymal transition in HCC to suppress tumour progression [10].…”
Section: Introductionmentioning
confidence: 99%